2021
DOI: 10.1038/s41598-021-84527-9
|View full text |Cite
|
Sign up to set email alerts
|

Bank vole prion protein extends the use of RT-QuIC assays to detect prions in a range of inherited prion diseases

Abstract: The cerebrospinal fluid (CSF) real-time quaking-induced conversion assay (RT-QuIC) is an ultrasensitive prion amyloid seeding assay for diagnosis of sporadic Creutzfeldt–Jakob disease (CJD) but several prion strains remain unexplored or resistant to conversion with commonly used recombinant prion protein (rPrP) substrates. Here, bank vole (BV) rPrP was used to study seeding by a wide range of archived post-mortem human CSF samples from cases of sporadic, acquired and various inherited prion diseases in high th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…A possible inhibitory effect has been described in a CSF sample with a total protein concentration higher than 0.45 g/L [28]. Tze How Mok et al showed, using post-mortem CSF samples, that only 70 of 79 sCJD samples and 9 of 20 various inherited prion diseases were positive, using undiluted post-mortem CSF in RT-QuIC with bank vole prion protein as substrate [29]. The lower sensitivity could be due to the high protein concentration in the post-mortem samples.…”
Section: Discussionmentioning
confidence: 99%
“…A possible inhibitory effect has been described in a CSF sample with a total protein concentration higher than 0.45 g/L [28]. Tze How Mok et al showed, using post-mortem CSF samples, that only 70 of 79 sCJD samples and 9 of 20 various inherited prion diseases were positive, using undiluted post-mortem CSF in RT-QuIC with bank vole prion protein as substrate [29]. The lower sensitivity could be due to the high protein concentration in the post-mortem samples.…”
Section: Discussionmentioning
confidence: 99%
“…Due to transmission barriers hamster or murine cells are generally restricted to infection with species-adapted prion strains. Bank voles, however, were found to be universal acceptors for prions 17 making them fast in vivo models for CJD 18 as well as CWD 19 , but also broaden the application area of in vitro assays like real-time quaking induced conversion (RT-QuIC) 20 , 21 and protein misfolding cyclic amplification (PMCA) 22 . So far only two cell lines expressing bank vole PrP were engineered being susceptible to murine scrapie (22L) and native CWD 23 , but no primary bank vole cell culture infectible with prions exists to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Two additional substrates, the sheep-hamster chimeric rPrP and in particular the bank vole (Bv) rPrP23-230 ( Cramm et al, 2015 ; Orrú et al, 2015b ; Mok et al, 2021 ), demonstrated a diagnostic potential despite their high reactivity and self-aggregating predisposition. Bank voles and transgenic mice expressing Bv rPrP are highly susceptible to many prion strains ( Nonno et al, 2006 ; Watts et al, 2014 ).…”
Section: The Real Time Quaking-induced Conversion Assaymentioning
confidence: 99%
“…Bank voles and transgenic mice expressing Bv rPrP are highly susceptible to many prion strains ( Nonno et al, 2006 ; Watts et al, 2014 ). Following a first successful attempt to convert BSE prions in the skin of 2 vCJD patients using Bv rPrP ( Orrú et al, 2017 ), in a recent study, 1 out 2 CSF samples collected post-mortem from vCJD cases was also positively converted by Bv rPrP ( Mok et al, 2021 ). However, the calculated sensitivity (88.6%) and specificity (91.2%) in the overall study cohort were below the mean of those reported in previous studies using traditional substrates ( Table 3 ).…”
Section: The Real Time Quaking-induced Conversion Assaymentioning
confidence: 99%